AUTO METRO TRAIN - AL-Talahmah, Besan; AL-Makhammrah, Aseel (جامعة بوليتكنك فلسطين - انظمة حاسوب, 2019)
Nowadays, modern technologies are helpful in all aspects of our life. Due to this, lots of development is done in the field of transportation. In previous years, with the use of regular trains, accidents occur due to various reasons, like human error, a signal errors and some other major problems. Human-operated metro trains have no control over time, which leads to missing the train schedule and affects the railway network management system. To solve this problem, we have built a prototype for a driverless metro train. Driverless metro train improves the management system of the railway network, reduces human errors, consumes less power and it provides comfort and safety to passengers during their travels
no of pages 55 , هندسة حاسوب 1/2019
Keywords: AUTO TRAINS